1992
DOI: 10.1038/jcbfm.1992.105
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cerebral Blood Flow in Anemic Patients on Long-Term Hemodialytic Treatment

Abstract: Summary: CBP was measured in 15 patients on chronic hemodialytic treatment. CBP was measured with xenon-133 inhalation using single photon emission tomography. In addition, computerized tomography (CT) and a neuro logical examination were done prior to hemodialysis. Mean CBP was 66.2 ± 17.3 (SD) ml 100 g-I min-I, which was significantly higher (t-test, p < 0.05) than for an age-matched control group (54.7 ± 10.2 ml 100 g-I min -I). However, the hematocrit for the patients was considerably lower, 0.30 ± 0.07, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
43
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 23 publications
6
43
2
Order By: Relevance
“…[7][8][9][10][11][12][13] As well as causing a global increase in cardiac output, chronic anemia also increases the CBF. 6,18,19 Volstrup et al, 6 in their observation with single-photon emission tomography for the CBF in long-term hemodialytic patients with CRF, found a significant negative correlation between CBF and hematocrit level. This result is an expected consequence of hemodynamic changes occurring in chronic anemia that was also detected in our study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[7][8][9][10][11][12][13] As well as causing a global increase in cardiac output, chronic anemia also increases the CBF. 6,18,19 Volstrup et al, 6 in their observation with single-photon emission tomography for the CBF in long-term hemodialytic patients with CRF, found a significant negative correlation between CBF and hematocrit level. This result is an expected consequence of hemodynamic changes occurring in chronic anemia that was also detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Although it was not measured in our study, cardiac output increase is a recognized issue in chronic anemia. 6,18,19 Eicke et al, 20 who established extracranial Doppler sonography for the measurements, found no association between common carotid artery blood flows and cardiac output. Because they did not include VAs in their measurements, it does not seem possible to make any comment on CBF in their study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations